THE ORIENTATION OF NEW TEXTBOOKS FROM THE COURSE «GENERAL GEOGRAPHY» IN THE FORMATION OF PUPILS’ INDEPENDENT WORK SKILLS - Sl’oza, Natalia V. (Educological discourse, 2015)
This article provides a characteristic of the essence and features of pupil’s independent work in the educational process of geography. The names of scientists working on the problem and the results of their researches are mentioned. The role of a new textbook in the effective formation of 6 Grade pupils’ independent work skills is determined. Author determined possibilities of new educational editions to the course "General Geography" for the implementation independent work activities by pupils and the formation of skills to it with the help of textbook. It is proved that the newly created geography textbook for 6 grade is a model that reflects the goals, principles, content and technology of learning in secondary school.